(untitled) (CIPEEX, 2025)
The Wells Bench "sit and reach" flexibility test is widely used to assess trunk flexibility and the flexibility of the hamstring muscles. The test involves sitting with the legs extended and feet flat on the ground, forming a 90-degree angle, and then leaning forward to slide the hands along the scale of the bench as far as possible. This method is effective for measuring range of motion and providing an objective assessment of flexibility. The present study aimed to analyze the flexibility of adolescents aged 13 to 15 years in a soccer school in the city of Ceres – GO. The Wells Bench evaluation parameter was used with the goal of observing changes in the range of motion of the students both at rest and after stretching sessions, specifically targeting the flexibility of the hamstrings and lower back. The results of the study indicate a significant improvement in the flexibility of the hamstrings and lower back following the stretching exercises. However, it is important to note that some athletes did not show improvements in their post-stretching results, which could be attributed to individual variables such as adherence to the stretching protocol, the intensity and duration of the stretches, and the initial flexibility condition of each individual. Previous studies support that specific stretching contributes significantly to increased muscle flexibility. According to the literature, improved flexibility can lead to several benefits, including enhanced agility, improved posture, and better muscular performance during physical activities. Additionally, adequate flexibility is crucial for injury prevention, as more flexible muscles and tendons can better withstand the stresses and strains during physical exercise. Therefore, the data suggest that implementing specific stretching routines could be a vital component in the training of young athletes, promoting not only improvements in flexibility but also functional and preventive benefits that can positively influence athletes’ performance and overall health.